Challenges of Resolving Land Dispute Conflicts in Puncak Siosar, Karo District - Lumbanraja, Victor (Journal of Peasants' Rights, 2023)
The agrarian conflict in North Sumatra has created persistent problems regarding various issues regarding the distribution of land to third parties without the local community, and the difficulty of the land titling process. One of the areas of agrarian conflict in North Sumatra is Puncak Siosar 2000. Puncak Siosar 2000 is an empty land disputed between the community and the company because the community is not aware of land ownership issues. The research method used is descriptive qualitative with a literature study approach in answering the government's role in resolving agrarian conflicts. The results show that the conflict at Puncak Siosar 2000 has led to physical conflict which has had a detrimental impact on society. Certainty of tenure and activities in conflict areas are the main triggers for land conflicts. Local government efforts to resolve conflicts require a sustainable strategy. Although the efforts made tend to prevent physical conflict and try to find a solution in finding a middle ground. Legal certainty and a persuasive approach strategy can be a solution in conflict resolution.